Pengungkapan Makna Biaya dalam Tradisi Maulid Nabi Dimasjid Sa’addatuddarain Desa Kotakusuma - Dwi Syafira Novianti; Syaiful Syaiful (Universitas 45 Surabaya, 2024)
This study aims to reveal the meaning of the cost of the Prophet's Mawlid tradition at the Sa'addatuddarain Mosque in Kotakusuma village by using three informants to examine the expression of the meaning of costs in the Prophet's Mawlid tradition. This research was conducted because it wanted to provide knowledge to the wider community that accounting is not only about a company but also has many fields. This research uses qualitative methods with a phenomenological research approach. The results showed that the meaning of cost in the tradition of the Prophet's Mawlid has a meaning as a means of unity and commitment for Muslims. The cost of celebrating the Prophet's Mawlid in Kotakusuma Village is a symbol of sacrifice, togetherness, and concern for the people. According to this research, the cost of Mawlid Nabi in Kotakusuma Village is not only a financial aspect but also a manifestation of deep values. And financial contribution is not only the fulfillment of the needs of the event but a tangible manifestation of the appreciation of these values.